Antibody and delayed-type hypersensitivity responses to Ochrobactrum anthropi cytosolic and outer membrane antigens in infections by smooth and rough Brucella spp. - Velasco, J (1997)
Immunological cross-reactions between Brucella spp. and Ochrobactrum anthropi were investigated in animals and humans naturally infected by Brucella spp. and in experimentally infected rams (Brucella ovis infected), rabbits (Brucella melitensis infected), and mice (B. melitensis and Brucella abortus infected). In the animals tested, O. anthropi cytosolic proteins evoked a delayed-type hypersensitivity reaction of a frequency and intensity similar to that observed with B. melitensis brucellin. O. anthropi cytosolic proteins also reacted in gel precipitation tests with antibodies in sera from Brucella natural hosts with a frequency similar to that observed with B. melitensis proteins, and absorption experiments and immunoblotting showed antibodies to both Brucella-specific proteins and proteins common to Brucella and O. anthropi. No antibodies to O. anthropi cytosolic proteins were detected in the sera of Brucella-free hosts. Immunoblotting with sera of Brucella-infected sheep and goats showed immunoglobulin G (IgG) to Brucella group 3 outer membrane proteins and to O. anthropi proteins of similar molecular weight. No IgG to the O-specific polysaccharide of O. anthropi lipopolysaccharide was detected in the sera of Brucella-infected hosts. The sera of sheep, goats, and rabbits infected with B. melitensis contained IgG to O. anthropi rough lipopolysaccharide and lipid A, and B. ovis and O. anthropi rough lipopolysaccharides showed equal reactivities with IgG in the sera of B. ovis-infected rams. The findings show that the immunoresponse of Brucella-infected hosts to protein antigens is not necessarily specific for brucellae and suggest that the presence of O. anthropi or some related bacteria explains the previously described reactivities to Brucella rough lipopolysaccharide and outer membrane proteins in healthy animals.